#instaworthy presentations of place: a place study of experience among teenagers on Instagram - Hughes, Fan E., author; Champ, Joseph, advisor; Humphrey, Michael, committee member; Badia, Lynn, committee member (Colorado State University. Libraries, 2019)
The present study is devoted to the exploration of place presentations and online representations of immersive place-based experiences by teenagers on Instagram. This study is curious to understand if students' from an international travel program, Rustic Pathways, presentations of place online are different or similar than descriptions of place experience offline and if these representations differ, why? The humanistic geography concept of 'place' and place attachment theory was used as a guiding framework for this study. This study employed a mixed methods approach, completing fifteen interviews with former Rustic Pathways students and textual analysis of ninety Instagram posts. The analysis applied multiple lenses of interpretation through a hermeneutic perspective as well as a critical textual analysis to understand both the constructed realities of place experience and to addresses the structures at work beyond individuals' actions within texts. After an extensive investigation into the phenomenon of place experience and place presentations on Instagram of Rustic Pathways participants on Instagram, I illustrate the place experience reflections as communicated by Rustic Pathways interview subjects. I also explore the interview subjects' descriptions of how their identity, values, and behaviors were influenced by place. I next explore the intersection of place and identity as observed on the Instagram platform. I examine how the data introduces conflicts in the communication of identity and experience as impacted by curated and invisible narratives, the discursive expectations of Rustic Pathways on the interview subjects and user's presentation of experience, as well as the influences of performativity on online representations of wild and exotic places. Finally, I explore the digital negotiations of place experience by examining the complexities of communicating offline experiences in an online space through identity performances.